Morphological Complexity and Prosodic Minimality - Laura J. Downing (Universitat Autònoma de Barcelona, 2005)
It is widely attested, cross-linguistically, for both words and prosodic morphemes to be required to be minimally bimoraic or disyllabic. Work since McCarthy and Prince (1986) argues that these minimality effects fall out from the Prosodic Hierarchy. Requiring the relevant morpheme to be a Prosodic Word and dominate a stress Foot automatically also imposes a two mora or two syllable minimality requirement. In this paper I show, based on a reanalysis of reduplication in Axininca Campa, that this Prosodic Hierarchy-based theory of minimality is inadequate. I argue instead that morphological minimality conditions are better explained as a form of Head-Dependent Asymmetry (Dresher and van der Hulst 1998). Head morphemes are enhanced by requiring more complex prosodic structure, mirroring their more complex morphological structure. This alternative approach not only provides a uniform account of minimality effects holding for Axininca Campa reduplication, it also solves the problems raised by McCarthy and Prince’s (1993, 1995) analysis of the data.